Inspecting sector-specific capital structure determinants: the case of Malaysian Shariah firms - Raja, Rehan; Adam Sa'ad, Auwal; Haron, Razali; Qazi Muhammad, Adnan Hye (Online Academic Press, 2023)
This study is set to inspect sector-specific capital structure determinants for publicly listed Malaysian Shariah-tagged firms. For this purpose, a 17-year data sample set comprising 343 Shariah firms in Bursa Malaysia’s main market is constructed. The seven key determinants, namely fixed assets, non-debt tax shield, current assets, growth, return on equity, size, and earnings per share, are measured as capital structure determinants in relation to the debt- equity ratio. Deploying a Dynamic Panel Data Model via an efficient econometric assessor, i.e., Generalized Method of Moments, the investigation exposes that current and fixed assets are observed as the key significant sector-specific capital structure determinants for Malaysian Shariah-tagged firms. Also, the positive and significant lagged dependent variables of each studied sector indicate the presence of a targeted capital structure and Speed of Adjustment (SOA). The occurrence of SOA explains variations in the debt-equity choices of Malaysian Shariah firms at the sector level. The significant tangibility and liquidity in most sectors and the significant lagged dependent variables across all sectors directly suggest the significance of the dynamic theory of Trade-Off. As a whole, it is observed that the sector-level capital structure framing practices of Shariah-tagged firms are not similar. This study aims to investigate the optimal debt-equity mix for listed Malaysian Shariah- complaint enterprises operating in diverse sectors. The observed outcomes are the baseline for policymakers to formulate a better financing model that supports Malaysian Shariah firms to maintain a dynamic or targeted capital structure at all times.